Respostas

  • PeH
  • Ambicioso
2013-06-05T18:28:17-03:00

Se:

 

• f(1) = 5, x, ao ser substituído por 1, produzirá um y/f(x) igual a 5

• f(-3) = -7, x, ao ser substituído por -3, produzirá um y/f(x) igual a -7

 

Assim, temos:

 

\begin{cases} 1a + b = 5 \\ -3a + b = -7 \end{cases} \\\\\\ \begin{cases} b = 5 - a \\ -3a + 5 - a = -7 \end{cases} \\\\\\ \begin{cases} b = 5 - a \\ -4a = -12 \end{cases} \\\\\\ \begin{cases} b = 5 - a \longrightarrow b = 5 - 3 = 2\\ a = 3 \end{cases} \\\\\\ \boxed{a = 3 \ \text{e} \ b = 2}

 

 

2013-06-06T16:22:04-03:00